Multilevel regulation of anthocyanin-promoting R2R3-MYB transcription factors in plants - Yang, Jianfei; Chen, Yunzhu; Xiao, Zhihong; Shen, Hailong; Li, Yuhua; Wang, Yu (Frontiers in Plant Science, 2022)
Anthocyanins are common secondary metabolites in plants that confer red, blue, and purple colorations in plants and are highly desired by consumers for their visual appearance and nutritional quality. In the last two decades, the anthocyanin biosynthetic pathway and transcriptional regulation of anthocyanin biosynthetic genes (ABGs) have been well characterized in many horticultural plants. From numerous studies on model plants and horticultural crops, many signaling regulators have been found to control anthocyanin accumulation via regulation of anthocyanin-promoting R2R3-MYB transcription factors (so-called R2R3-MYB activators). The regulatory mechanism of R2R3-MYB activators is mediated by multiple environmental factors (e.g., light, temperature) and internal signals (e.g., sucrose, ethylene, and JA) in complicated interactions at multiple levels. Here, we summarize the transcriptional control of R2R3-MYB activators as a result of natural variations in the promoter of their encoding genes, upstream transcription factors and epigenetics, and posttranslational modifications of R2R3-MYB that determine color variations of horticultural plants. In addition, we focus on progress in elucidating the integrated regulatory network of anthocyanin biosynthesis mediated by R2R3-MYB activators in response to multiple signals. We also highlight a few gene cascade modules involved in the regulation of anthocyanin-related R2R3-MYB to provide insights into anthocyanin production in horticultural plants.